Skin Penetration and Stability Enhancement of Celastrus paniculatus Seed Oil by 2-Hydroxypropyl-β-Cyclodextrin Inclusion Complex for Cosmeceutical Applications - Warintorn Ruksiriwanich; Jakkapan Sirithunyalug; Chiranan Khantham; Krot Leksomboon; Pensak Jantrawut (MDPI AG, 2018)
This study aimed to encapsulate Celastrus paniculatus seed oil (CPSO) in 2-hydroxypropyl-β-cyclodextrin (HPβCD) cavities and investigate their biological activity, physicochemical stability, and skin penetration by vertical Franz diffusion cells of the CPSO-HPβCD inclusion complex formulations. For biological activity studies—including 2,2-diphenyl-1-picryhydrazyl radical (DPPH) scavenging, metal ion chelating, and inhibition of lipid and tyrosinase inhibition activities—the CPSO-HPβCD inclusion complex exhibited lower inhibition activity than free CPSO. CPSO-HPβCD dispersion, serum, and gel formulations were prepared. All formulations containing the CPSO-HPβCD inclusion complex showed no significant changes in physical characteristics after three months’ storage. The percentages of oleic acid remaining in all formulations were over 80% of the initial amount during a three-month stability study. For the skin-penetration study, compared to other formulations, the CPSO-HPβCD serum formulation exhibited the highest cumulative amount of oleic acid in the whole skin and flux through receptor fluid, after six hours, of 32.75 ± 1.25 µg/cm2 and 1.02 ± 0.15 µg/cm2/h, respectively. The CPSO-HPβCD serum formulation also showed the proper viscosity. Hence, the CPSO-HPβCD inclusion complex will be beneficial for the further development of cosmeceutical products.